منهج عثمان تشاو تشونغ شي في ترجمة معاني القرآن الكريم إلى اللغة الصينية وتفسيره - ما، يي قانع (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
This thesis explores the work of Osman Zhou Zhongxi (born 1925CE) who translated the Qurʼan from Arabic to Chinese and supplied it with his interpretation of the Quranic verses. The work has been a matter of dispute amongst the Chinese community between those who celebrated it and those who criticized its content. This is due to Osman being seen as propagating the ideas promoted by the Qadiani sect which contradict the orthodoxy. The researcher traces Osman's words that engage with the Qadiani's thought throughout his translation and interpretation. The research is carried out by adopting the descriptive and analytical methods. The aim is to introduce Osman Zhou and his work to the Chinese community and highlight the controversial views mentioned in this work. The research consisted of several chapters detailing the life of Osman Zhou, the background of his work, the methodology of Osman Zhou in some subjects of the sciences of Qurʼan (ʻulum al-Qurʼan) and the principles of exegesis (qawaʻid al-tafsir), and examples of his texts concerning topics related prophethood, the matters of the unseen, the miracles of the prophets, and the pillars of Islam. The research confirms the connection between Osman Zhou and the Qadiani's thought in his translation and interpretation of the Qurʼan.